Analisis Pengaruh Gender, Gaya Kepemimpinan dan Budaya Organisasi terhadap Produktivitas Sekolah Dasar Negeri di Kabupaten Sidoarjo - Tantri Widiastuti; Margono Setiawan; Muhammad Syamkhin (Jurnal Aplikasi Manajemen, 2012)
School productivity can be increased by improving the leadership professionalism of school principal. Principal leadership will influence other parties in school. The objective of research is (1) understanding the simultaneous effect of variables of gender, leadership style, and organizational culture on elementary school productivity, (2) acknowledging the partial effect of variables of gender, leadership style, and organizational culture on elementary school productivity, and (3) figuring out which variables with the most dominant effect on elementary school productivity. Research type is explanatory research besause it reviews about the effect of independent variable on dependent variable, and formulates the hypotheses. The sample is 83 principals of elementary school at Sidoarjo Regency. Data analysis is multiple regression analysis with dummy variable. Result of research indicated that : (1) gender, leadership style, and organizational culture can increase school productivity, especially at elementary school in Sidoarjo Regency; (2) there is no different effect between male and female principals on elementary school productivity. If a principal as school superior employs appropriate leadership style in leading the school, it will improve school productivity. Organizational culture also supports the productivity improvement because it stimulates superior and subordinate indirectly to produce a cooperation to regulate the attitude and behavior to be adjusted ti the vision and mission of school strategy; and (3) in comparing organizational culture and leadership style, organizational culture gives greater contribution for school productivity improvement. The culture also empowers principal’s competence to increase subordinate’s motivation in applying school strategy.Keywords: Gender, Leadership Style, Organizational Culture, School Productivity